The Effectiveness Of Digital Phonic Literacy In Improving The Reading Basics Of Grade II Students Of Gugus 7 Seririt - Gusti Ayu Made Ariwimarsi; I Putu Sanjaya; Ni Nyoman Kurniawati (Jurnal Pendidikan Dasar dan Keguruan, 2026)
This study aims to determine the effectiveness of using digital phonics literacy media in improving the basic reading concept skills of second-grade students in Cluster 7, Seririt District. The research is motivated by the low initial reading ability of elementary school students, which is often caused by the limited availability of interactive and engaging learning media. This study employs a quantitative approach with a quasi-experimental design, utilizing a one–group pretest–posttest design. The research subjects were 26 students selected using a total sampling technique. Data were collected through a basic reading concept ability test given before and after the implementation of digital phonics literacy media. Data analysis was conducted using descriptive and inferential statistics, including normality tests, homogeneity tests, and paired sample t-tests, with the assistance of SPSS version 29.0. The study's results showed an increase in students' reading ability, as indicated by a rise in the average score from 31.92 in the pretest to 72.81 in the posttest. The results of the hypothesis test showed a significance value <0.05, which indicates a significant difference between students' reading ability before and after treatment. Thus, it can be concluded that digital phonics literacy media are effective in improving the basic concepts of reading skills among elementary school students.